Measuring a family sense of coherence: a rasch-based study extending dyadic data analyses - Marie-Louise Möllerberg; Kristofer Årestedt; Peter Hagell; Jeanette Melin (BMC Palliative Care)
Abstract Background Family sense of coherence (FSOC) seems to reduce distress in the family and promote the well-being of the family. Therefore, getting accurate measurements for families with long-term illnesses is of particular interest. This study explores dyadic data analysis from the dyadic- and single-informant perspectives, and the measurement properties of the FSOC-S12 according to the Rasch model. Methods Racked and stacked data from 151 dyads were analyzed according to the polytomous Rasch model. Results Notably, both the dyadic- and single-informant perspectives (i.e., racked and stacked data set-ups) showed measurement properties with minor deviations from the Rasch model according to fit statistics. However, most items had disordered thresholds and some problems with local dependency. Item hierarchies were similar in both set-ups and there was no differential item functioning (DIF) by role from the dyadic informant perspective. Four items showed DIF by informant role in the single-informant perspective. Conclusions Our approach to handling dyadic data has shown both strengths and limitations in the evaluation of FSOC-S12, and the understanding of FSOC as a construct from the family’s view of the family’s ability as a whole (dyadic-informant perspective) and patient’s and family member’s separate views of the family’s ability as a whole (single-informant perspective).